Dissolution of kraft lignin in alkaline solutions - Melro, Elodie (2020)
Lignins are among the most abundant renewable resources on the planet. However, their application is limited by the lack of efficient dissolution and extraction methodologies. In this work, a systematic and quantitative analysis of the dissolution efficiency of different alkaline-based aqueous systems (i.e. lithium hydroxide, LiOH; sodium hydroxide, NaOH; potassium hydroxide, KOH; cuprammonium hydroxide, CuAOH; tetrapropylammonium hydroxide, TPAOH and tetrabutylammonium hydroxide, TBAOH) is reported, for the first time, for kraft lignin. Phase maps were determined for all systems and lignin solubility was found to decrease in the following order: LiOH > NaOH > KOH > CuAOH > TPAOH > TBAOH, thus suggesting that the size of the cation plays an important role on its solubility. The π∗ parameter has an opposite trend to the solubility, supporting the idea that cations of smaller size favor lignin solubility. Dissolution was observed to increase exponentially above pH 9-10 being the LiOH system the most efficient. The soluble and insoluble fractions of lignin in 0.1 M NaOH were collected and analyzed by several techniques. Overall, data suggests a greater amount of simple aromatic compounds, preferentially containing sulfur, in the soluble fraction while the insoluble fraction is very similar to the native kraft lignin.